Privatization, law, and the challenge to feminism - Cossman, Brenda, 1960-; Fudge, Judy (University of Toronto Press, 2002)
Examining eight case studies on the role of law in various arenas, this collection of essays addresses the reconfiguration of the relations between the state, the market, and the family caused by privatization.